Telejournal FOCA ON TV, Innovation in Telejournalism: An educommunication experience in the era of mobile technology - Gomes, Sandra Maria de Morais; Baptaglin, Leila Adriana (Seven Editora, 2023)
This construction seeks to point out the directions of Educommunication in Higher Education through innovation processes and its interface with Mobile technology. The objective is to characterize the creation of the FOCA NA TV newscast as a hybrid experience between professional equipment with the smartphone and the production and editing of articles made by students of the disciplines of Telejournalism of the Federal University of Roraima, UFRR. We show that Educommunication appears in the process, pointing out new forms of teaching-learning and reordering new methods for the institutions of Public Higher Education in Roraima. It points out how mobile technology impacts journalism and how Educommunication and its interdisciplinarity bring innovation through its interface with mobile technology. DOI:https://doi.org/10.56238/alookdevelopv1-175